Queens Around the World, 1520–1620 - Ze’evi, Dror. author. aut Link
XV, 297 p.
Keywords: This textbook explores the histories of royal women in Europe, the Middle East, and parts of Asia in the sixteenth and early seventeenth centuries. It argues that by dint of an unprecedented conjunction of historical shifts and powerful personalities, it was these women, and not men, who sat at the helm of global politics; moreover, it was they who in truth steered our world’s transition from the Middle Ages to modernity. Organized into chapters devoted to each of the era’s great states, the book sets out to challenge several historical premises. First, it shows that women were the actual, if not always formally crowned, sovereigns of these states, or at least played a decisive role in shaping their policies. Second, the book dissolves the conventional dichotomy between East and West, showing that in both Christian Europe and Islamdom, women achieved their high status by means of similar strategies and at similar periods in history. Third, by demonstrating that there was a precedent for female authority long before the first harbingers of the women’s movement in the eighteenth century, the book calls into question received ideas about historical progress and the evolution of women’s liberation.